Chlordiazepoxide induced Stevens-Johnson syndrome in acute pancreatitis - Ramineni, Hari Babu; Boppudi, Bhuvana; B, Silviya Grace; Yerramaneni, Rakesh; Suryadevara, Vidyadhara (International Journal of Research in Medical Sciences, 2017)
Stevens-Johnson Syndrome (SJS) is an acute hypersensitive reaction and a life-threatening condition affecting both skin and mucous membranes. We report a case with SJS likely induced by Chlordiazepoxide. The patient undergoing treatment for acute pancreatits is prescribed with Chlordiazepoxide after administering the patient reported mild pyexia with lesions all over the body with redness. Mild peeling of the skin due to rupture of the lesions and pigmentation on the skin was observed for 3 days. Based on these finding he was diagnosed with Chlordiazepoxide induced Stevens-Johnson syndrome. The patient was administered systemic steroid therapy and treated symptomatically. Here we describe a case of Chlordiazepoxide induced SJS in acute pancreatitis patient.